Domino [videorecording (DVD)] - Scott, Tony, 1944-2012; Knightley, Keira, 1985-; Liu, Lucy, 1968-; Rourke, Mickey; Walken, Christopher, 1943- (New Line Home Entertainment : Distributed by Warner Home Video, 2006)
Based on the true story of Domino Harvey, who is the daughter of film actor Laurence Harvey. Tired and unsuited to the pretentiousness of her high-society Los Angeles life, Domino leaves the glitz behind her and sets off to become a bounty hunter. She quickly falls under the wing of veteran hunter Ed Mosley and his crew, becoming an unlikely natural in the art of bounty hunting. But things heat up when a gang of masked men begin a series of armored car heists. Before long the mob, a crazed TV producer, the FBI and a terminally ill child have all got caught up in the crazy situation.